Robot roll call - Frantz, Jennifer (New York, NY : HarperCollins, 2008)
"Meet the new generation of robots in disguise! Optimus Prime and the Autobots have made some great new friends, but the Decepticons are up to their usual trouble! Join them all as they begin their adventures in a strange land- - Earth!"--P. [4] of cover.
"2, reading with help."
"Based on the new television show"--Cover.
Keywords: Transformers (Fictitious characters) -- Juvenile fiction; Robots -- Juvenile fiction; Science fiction; Readers (Elementary); Radio and television novels